Effect of local preparations containing glucocorticoids on local immunity parameters and activity of human papillomavirus - E I Borovkova; A S Fedotova (IP Berlin A.V., 2017)
The aim of the study was to investigate the effects of topical application of preparations containing glucocorticoids on the replicative activity of human papillomavirus oncogenic type. Prospective study included 160 patients of reproductive age. The examination included microbiological testing, qualitative and quantitative screening for human papilloma virus high-risk group (HPV-PCR and Digene-test), immunological study of cervical secret (immunoglobulins class A, M, G and secretory IgA). Was shown that the vaginal microbiocenosis in patients with nonspecific vaginitis presents a wide range of opportunistic microorganisms, such as Staphylococcus, Streptococcus, Peptostreptococcus, Bacteroides, Bacillus, Actinomyces, Corynebacterium, Prevotella. A number of typical representatives of the indigenous microflora is significantly reduced, or absent. The prevalence of concomitant viral infection was approximately 29%, the most frequently detected viruses 16, 31 and 18. The use of local therapy drug containing a glucocorticoid qualitative and quantitative changes in HPV have been no identified. Evaluation of indicators of local immunity showed an imbalance in the production of immunoglobulins with a predominance of IgA, secretory IgA and IgG in patients on the background of nonspecific vaginitis.